Standardisation of partial strength connections of flush end plate connections for trapezoid web profiled steel sections - Md. Tahir, Mahmood; Sulaiman, Arizu; Mohamed, Shaharin; Saggaf, Anis (The Institution of Engineers, Malaysia, 2006)
Connections are usually designed as pinned or rigid although the actual behaviour is known to fall between these two extreme cases. The use of partial strength or semi-rigid connections has been encouraged by codes. Studies on the matter known as semicontinuous construction have proven that substantial savings in steel weight of the overall construction can be achieved. The objective of this paper is to develop a series of standardised partial strength connections tables of flush end-plate connections for trapezoidal web profiled steel (TWP) sections. The range of standard connections presented in tabulated form is limited to six tables comprised of different geometrical aspects of the connections. These tables could enhance the design of semi-continuous construction of multi-storey braced steel frames. The connections are presented in the form of standardised tables which include moment capacity and shear capacity after considering all possible failure modes. The moment capacity, shear capacity, geometrical aspects of the connections, the size of beams, and columns that are suitable with the connections are included in the standardised tables. A method proposed by Steel Construction Institute(SCI) which take into account the requirements in Eurocode 3 and BS 5950:2000 Part 1 were adopted to predict the moment capacity and shear capacity in developing the tables. This proposed method has been successfully applied to the establishment of standardised connections tables for hot-rolled British sections. Although the use of the proposed method is intended for hot rolled section, it is also possible to apply the same proposed method to TWP section provided that the predicted failure modes should comply with the requirements of Eurocode 3 and BS 5950:2000 Part 1 and the TWP section should at least classified as compact section. The moment capacity and shear capacity in the standard tables presented in this paper showed good agreement with the requirement of Eurocode 3 and BS 5950:2000 Part 1.